Association between characteristics of mammographic calcifications and malignie Neoplasia in a national hospital – 2017: Asociación entre características de las calcificaciones mamográficas y neoplasia maligna en un hospital nacional, 2017 - Arteaga-Huanca, Víctor (2019)
Introduction: The presence of calcifications may be useful for the diagnosis of breast neoplasia. Objective: To determine the association between the characteristics of mammographic calcifications and malignant neoplasia. Methods: Observational, analytical, retrospective of cases and controls. Developed in the Gynecology Breast Pathology Unit. Female patients with mammogram suggestive of malignant neoplasm with a positive malignancy biopsy were included as cases, and 67 patients without histological evidence of malignancy as controls. Results: The average age of the cases was 54.12 years, in the controls 50.34. 50,.9% (59) are older than or equal to 50 years, OR 2,399 95% CI (1,125-5,114) p = 0.022, of these 52.5% (31) had breast cancer. 9.5% (11) had calcifications suspicious of malignancy, the most frequent, the amorphous and the pleomorphic fine. 37.1% (43) of the total cases have the BI-RADS 0 category, 6.9% (8) BI-RADS 1, 8.6% (10) BI-RADS 2, 7.8 % (9) BI-RADS 3, 28.4% (33) BI-RADS 4, 8.6% (10) BI-RADS 5 and 2.6% (3) BI-RADS 6. 72, 7% (8) of patients with calcifications suspected of malignancy presented breast cancer. In the bivariate analysis, an OR of 4,163 was obtained. 95% CI (1,043-16,606) p = 0,031. In the multivariate analysis the association remained unchanged regardless of age and BI-RADS. Conclusion: Age 50 years or older and mammographic calcifications suspected of malignancy are associated factors for breast cancer.